Evaluation of post-operative analgesic efficacy of transversus abdominis plane block in patients who underwent caesarian section under spinal anesthesia - Karatepe, Umit; Ozer, Ayse Belin (Scientific Publishers of India, 2018)
Objective: In this study, we evaluated the efficacy of ultrasound guided Transversus Abdominis Plane Block (TAPB) procedure that was performed for the purpose of postoperative analgesia in patients who underwent caesarian section operation under spinal anesthesia. Patients and methods: This study included a total of 50 patients who underwent elective Caesarian section under spinal anesthesia. Patients were divided into two groups: those who postoperatively underwent guided ultrasound TAPB (Group TAPB, 20 ml. of 0.25% bupivacaine injected bilaterally); and those who did not undergo TAPB (Group C). Post-operatively, all patients received patient-controlled analgesia using tramadol. Visual Analog Scale (VAS) scores were recorded at the time of patient’s transport to and from the recovery room, and at the post-operative 1st, 2nd, 4th, 6th, 12th and 24th h. Tramadol consumption was recorded at the recovery phase and at 24 h. Results: Demographical data of the patients did not show any statistically significant difference. The amount of tramadol administered during recovery and at the end of postoperative 24 h were significantly lower in group TAPB (32.50 ± 15.51 and 226.00 ± 66.44 mg, respectively) in comparison to group C (47.52 ± 19.15 mg and 280.80 ± 35.34 mg, respectively) (p<0.01). VAS scores at time of transport to the recovery room, at the time of exit from the recovery room, and at the post-operative 1st, 2nd, 3rd, 4th, 6th and 12th h were significantly lower in group TAPB when compared to group C (p<0.05). Conclusions: It has been determined that ultrasound-guided TAPB performed after spinal anesthesia results in lower VAS scores, reduced analgesic consumption. © 2018, Scientific Publishers of India. All rights reserved.
Keywords: Caesarian section; Spinal anesthesia; Transversus abdominis plane block